2018
DOI: 10.3382/ps/pey022
|View full text |Cite
|
Sign up to set email alerts
|

Why did severe feather pecking and cannibalism outbreaks occur? An unintended case study while investigating the effects of forage and stress on pullets during rearing

Abstract: This 2 × 2 factorial experiment aimed to investigate the effects of stimulating foraging behavior from wk 6 and imposed stress at wk 16 on the development of severe feather pecking (SFP) in chickens reared for free-range egg production. Non-beak-trimmed ISA Brown chicks were purchased at one day old and floor-reared on wood shavings. From wk 6, straw was provided daily in dispensers (Forage vs. No forage) to stimulate foraging. At wk 15, there were 16 pens of 50 pullets. "Stressors" were applied to half the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 58 publications
0
17
0
1
Order By: Relevance
“…Provisioning of pecking substrate at young age may reduce the likelihood of sever feather pecking at maturity [6]. However, such provision does not completely eliminate the risk of severe feather pecking during adulthood [7]. Some studies have indicated that pecking is more severe in old laying hens (>70 weeks of age) when compared to young hens (25 weeks of age) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Provisioning of pecking substrate at young age may reduce the likelihood of sever feather pecking at maturity [6]. However, such provision does not completely eliminate the risk of severe feather pecking during adulthood [7]. Some studies have indicated that pecking is more severe in old laying hens (>70 weeks of age) when compared to young hens (25 weeks of age) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The farmers’ estimations about losses of egg production and mortality due to pecking problems appear to be moderate and, thus, are in line with their estimations of the level of existing pecking problems. Feather pecking does not typically lead to mortality or culling [5,15], but severe cases of cannibalism increase mortality [4,19,40]. According to reports, feather pecking [3,5] and cannibalism [4] negatively affect egg production, and feather loss due to pecking-related problems increases feeding costs [3], consequently leading to reduced income, thus negatively impacting sustainability.…”
Section: Resultsmentioning
confidence: 99%
“…Using structural equation models, Bessei et al (2018) could not confirm the hypothesis that foraging in young pullets is a cause for FP. Furthermore, a study by Cronin et al (2018) reported more injurious pecking and higher mortality in groups which received foraging material.…”
Section: Re-directed Behaviourmentioning
confidence: 99%